Competences of the professor of Information Science, Library Science and Archival Science in Latin America and Spain - Jaramillo, Orlanda (2017)
The paper addresses the competences of the professor in Information Science, Library Science and Archivology in Latin America and Spain from a mixed approach, where the documentary search shows the little tackled of the subject. Therefore, it points out the teaching profile should be viewed, reflected and evaluated from the competencies and skills; which is translated into the approach of curricular contents from the cognitive (to know), management-application (to do), attitudinal (to be) and communicative (to cohexist) dimensions. The work warns of the transversality of ICT in the curricula, where they play an important role as a tool in the disciplinary development. Consequently, a list of competences for the ICT area teacher is proposed from the components of the cognitive dimension.